Characteristics of track cycling - Craig, N. P.; Norton, K. I. (Sports Medicine, 2001)
Track cycling events range from a 200 m flying sprint (lasting 10 to 11 seconds) to the 50 km points race (lasting approximately 1 hour). Unlike road cycling competitions where most racing is undertaken at submaximal power outputs, the shorter track events require the cyclist to tax maximally both the aerobic and anaerobic (oxygen independent) metabolic pathways. Elite track cyclists possess key physical and physiological attributes which are matched to the specific requirements of their events: these cyclists must have the appropriate genetic predisposition which is then maximised through effective training interventions. With advances in technology it is now possible to accurately measure both power supply and demand variables under competitive conditions. This information provides better resolution of factors that are important for training programme design and skill development.